2015
DOI: 10.1515/med-2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon case of arterial aneurysms association with high plasma levels of Matrix Metalloproteinase-9 and Neutrophil Gelatinase-Associated Lipocalin

Abstract: The association of an axillary artery aneurysm and an abdominal aortic aneurysm is extremely rare. In this study, we describe this association in a 69 year-old-man. We measured this patient’s metalloproteinases (MMPs) and Neutrophil Gelatinase – Associated Lipocalin (NGAL) levels over a three years period before the abdominal aortic aneurysm rupture. We speculate that high serium levels of MMPs and NGAL may have a prognostic role and may predict aneurysm rupture in patients with an uncommon association of arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Several studies have shown that MPs participate in several steps of the development of AA [ 15 , 16 ]. Increased circulating levels of neutrophil gelatinase-associated lipocalin (NGAL) and MMP-9 have been documented in patients with AA [ 17 , 18 ]. Similarly, overexpression of several ADAMs and ADAMTS promotes AA development and expansion [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that MPs participate in several steps of the development of AA [ 15 , 16 ]. Increased circulating levels of neutrophil gelatinase-associated lipocalin (NGAL) and MMP-9 have been documented in patients with AA [ 17 , 18 ]. Similarly, overexpression of several ADAMs and ADAMTS promotes AA development and expansion [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An aneurysm develops in the setting of antecedent systemic infections with bacteremia or through the direct local invasion of the vessel wall (e.g., IV drug users) in the pre-existing aneurysm or atheromatous plaques [19]. The bacterial infection causes the release of pro-in ammatory cytokines, polymorphonuclear (PMN) leukocytes in ltration, and activation of matrix metalloproteinases, resulting in the focal vessel wall disintegration [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increased MMP activity is associated with a higher risk of aortic rupture [91].…”
Section: Pathogenesismentioning
confidence: 99%